(untitled) (Research, Society and Development, 2020)
Introduction: COVID-19 – a viral disease that has become a public health emergency – has SARS-CoV-2 as its etiological agent and is transmitted by droplets or aerosols from infected individuals. Due to the high rate of contamination by the virus and the limitations of the disease’s treatment, public and private institutions have been recommending the use of masks as a form of mass respiratory protection. Objective: to outline a broader overview of aspects related to the production, access, use and handling of homemade masks and to specify the time, form of use and recommendations for each type of professional mask. Methodology: For this purpose, an integrative literature review was carried out in PubMed, LILIACS, Web of Science, Scopus, Science Direct, The BMJ and LEXML’s databases, using various combinations of the main descriptors “masks”, “personal protective equipment” and “virus diseases”. Results: Among the main findings, the most effective protection of N95 and FFP2 respirators stand out, to the detriment of surgical masks. In addition, evidence shows efficient disinfection methods for respirators, such as the use of hydrogen peroxide and UV radiation, and the alternative of using handmade masks, inexpensive and easy to manufacture, for the general population, in face of individual protection equipment shortages. Conclusion: In the midst of a pandemic with a viral etiological agent, it is essential to study respiratory protection devices, differentiating them according to their particularities, in order to know the most suitable for individual and collective protection.